TANDA-TANDA ANTI KRISTUS DALAM PERSPEKIF ALKITAB - Frendsisco Frendsisco; Friska Gustina; Dea Riani Agustini; Sarmauli Sarmauli (JOURNAL SAINS STUDENT RESEARCH, 2025)
This article examines the signs of the Antichrist's presence from a biblical eschatological perspective. Using a theological approach and literature review, this study outlines the concept of the Antichrist as a manifestation of rebellion and misguidance against Christ. This study shows that the Antichrist is a symbol of resistance against God that will emerge before Christ's second coming to deceive believers. Through an analysis of biblical texts, particularly from 1 John, 2 Thessalonians, and Revelation, this study concludes that the presence of the Antichrist serves as a warning for believers to remain faithful, vigilant, and strong in their faith. The implications of this study encourage Christians to strengthen their faith and live according to the truth of God's word while awaiting Christ's return.